Development of Solar PV Systems for Mini-Grid Applications in Tanzania - Mayanjo, Seleman A.; Justo, Jackson J. (Tanzania Journal of Engineering and Technology, 2025)
Access to electricity offers great benefits to development through the provision of reliable and efficient energy sources in the country. Majority of the population living in the remote and rural areas of developing countries mostly sub-Saharan Africa are not supplied with electricity. Although the governments through their electricity companies put their effort to extends the grid distribution networks to remote and rural areas still the coverage were not sufficiently enough due to growing demands for safe and reliable electricity. However, solar as a source of energy remains the least utilized energy source in many countries including Tanzania. Solar Photovoltaic (PV) systems mini-grids have shown their potential in rural electrification projects in many countries mostly sub-Saharan Africa. A solar PV system mini-grid is a PV plant with a localized distribution network to a unit village, or a cluster of villages, providing alternating current (AC). Basically, it consists of solar PV modules of a certain capacity, charger controller, inverters for converting the DC power to AC power, housing for the battery bank and plant control systems. In areas where there is no grid connection or where diesel generation is the main power source, PV plants are able to generate electricity efficiently and relatively cheaply. This paper aims at giving out the overview of solar PV mini-grid applications in Tanzania basically, in terms of technical design and economic analysis of the selected mini-grid system at Juma Island village located in Sengerema District in Mwanza Region. The Juma Island settlements has the electricity demands estimated about 25 kWh per day. At the prevailing tariff conditions in the country, this project can be considered as financially viable with feed-in tariff scheme or other incentives such as grants/capital subsidies when applied. However, the other non-financial benefits like the greenhouse gas emissions savings can, in the long run, help mitigate the adverse effects of the climate change problem plaguing the entire earth.